Characteristics of Reproduction of Yellowstripe Scad Selaroides leptolepis (Cuvier, 1833) In Manado Bay Waters - Febrina Sinaga; Ferdinand F Tilaar; Nego E Bataragoa (Sam Ratulangi University, 2018)
The waters of Manado Bay are areas that have a lot of biological resources. One of these resources is Yellowstripe scad (Selaroides leptolepis). The research was aimed to find out the reproduction characteristics of Yellowstripe scad (Selaroides leptolepis) by looking at male and female sex ratio, growth pattern with male and female condition factor, maturity level of gonad (TKG), gonad maturity index (IKG), size at first maturity, and fecundity. The location of fish sampling is taken from the catch of fishermen in Manado Bay waters in not April-May 2018. Fish sampling using random draw method withdrawal. The number of samples is 200, taken four times in two months (April to May 2018). The sex ratio of Yellowstripe scad (Selaroides leptolepis) in the waters of Manado Bay is balanced. The growth pattern of male is positive allometric, while females is isometric. The condition of male and female fish are 0.9 and 1.3 respectively. The Yellowstripe scad breeding season in Manado Bay waters takes place after the fourth week in April. The size of the first time ripe gonad Yellowstripe scad male and female 189 mm. The fecundity ranged from 1,960 - 29,145 with an average of 11,716 ± 6,088.Keywords: Yellowstripe scad, reproductive biology, Manado Bay ABSTRAKPerairan Teluk Manado adalah perairan yang memiliki sumberdaya hayati cukup banyak. Salah satu sumberdaya di perairan tersebut yaitu ikan Selarkuning (Selaroides leptolepis). Penelitian itu bertujuan untuk mengetahui karakteristik reproduksi ikan Selarkuning (Selaroides leptolepis) dengan melihat dari rasio kelamin jantan dan betina, pola pertumbuhan dengan faktor kondisi pada jantan dan betina, tingkat kematangan gonad (TKG), indeks kematangan gonad (IKG), ukuran pertama kali matang gonad, dan fekunditas. Sampel ikan diambil dari hasil tangkapan nelayan di perairan Teluk Manado pada bulan April-Mei 2018. Pengambilan sampel ikan menggunakan metode penarikan secara acak berlapis. Jumlah sampel sebanyak 200 ekor, diambil empat kali dalam dua bulan. Berdasarkan uji Chi-square, rasio kelamin ikan Selarkuning (Selaroides leptolepis) di perairan Teluk Manado adalah seimbang. Pola pertumbuhan ikan Selarkuning yaitu bersifat allometrik positif, sedangkan betina bersifat isometrik dengan rata-rata faktor kondisi ikan jantan dan betina mencapai 0,9 dan 1,3. Musim pemijahan ikan Selarkuning di perairan Teluk Manado berlangsung setelah minggu keempat pada bulan April. Ukuran pertama kali matang gonad ikan Selarkuning jantan dan betina 189 mm. Fekunditas ikan Selarkuning berkisar antara 1.960 – 29.145 butir dengan rata-rata 11.716 ± 6.088.Kata kunci: ikan Selarkuning,biologi reproduksi, Teluk Manado